CONTACT STRESS AND CAGE STRENGTH ANALYSIS OF CONSTANT VELOCITY JOINT FOR OFF-ROAD VEHICLE UNDER BAD WORKING CONDITIONS - SONG YouShuo; MA Yue (Jixie qiangdu)
The load of ball cage type constant velocity joint of military off-road vehicle is larger than that of traditional vehicle, and the working condition is bad, which may cause contact wear, as well as the fracture of the cage under the angle between large axes. Therefore, it is very important to study the contact stress and the strength of the cage under the bad working condition. In this paper, a typical military off-road vehicle ball cage constant velocity joint is taken as the object. Firstly, the contact stress between the steel ball and the inside and outside raceway is theoretically analyzed and simulated. The simulation and analytical results are compared to verify the correctness of the simulation model. Secondly, according to the load transfer relationship between the key parts of the universal joint and the physical experiment, the reason and process of cage fracture are analyzed. Finally, the static torsion test under the ultimate axial angle is carried out, and the hardness test is carried out on the section of the cage. The strength distribution along the thickness is obtained through the relationship between hardness and strength conversion. The results show that the strength of the cage meets the requirements under normal working conditions, but may be broken under bad working conditions. This research can provide theoretical reference for the design and manufacture of constant velocity joint for off-road vehicle.